Karakteristik dan Pemanfaatan Gua-Gua Hunian Prasejarah di Perbukitan Karst Kotabaru, Kalimantan Selatan - Nia Marniati Etie Fajari; Anggraeni Anggraeni (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2022)
This study raises the issue of the characteristic and use of rock shelters and caves at the Batu Cave, Cililin Cave 1, and Jauharlin Cave 1 located in the karst area of ​​Kotabaru, South Kalimantan. Archaeological data was obtained by survey and excavation at the three sites. The analysis is carried out by compiling parameters consisting of 2 aspects, namely the physical cave and niche, and the characteristic of the findings. Analysis of the two parameters resulted in an interpretation providing an overview of the forms of utilization of the three caves studied. This study uses an ecological approach to understand that humans cannot be separated from their environment. The results showed that caves and niches had been used for two different activity components. Batu Cave, Cililin Cave 1, and Jauharlin Cave 1 were used for human inhabition that developed a Mesolithic-Neolithic culture 4000 years ago. Cililin Cave 1 was also used as a location for ironstone smelting workshops in the later period, which was around the 2nd century AD meanwhile, Jauharlin Cave 1 was used for the burial of Mongoloid humans in 530 AD.